Estimation of Suspended Sediment Load in the Ressoul Watershed, Algeria - Khanchoul, Kamel; Khanchoul, Skander (International Journal of Hydrology Research, 2019)
Sediment load and its response to the variations of the hydrological elements are important to understand the phenomena of erosion. This study was fulfilled with the aim of developing a model to predict sediment load using sediment rating curve for the Ain Berda gauging station. The model was developed based on the available streamflow discharge and suspended sediment concentration data during sampled storm events over 39 year-period in the Ressoul watershed. Relationships between sediment concentration and water discharge were used according to single and rising-falling stage ratings to determine the best model for sediment load prediction. Additionally, a technique was devised to correct for log-transform bias on the sediment rating curves. The mean annual sediment yield during high and medium high flood events was 302 T km-2 yr-1. The high sediment loads in the study basin could be explained by the intensity of rain, the aggressiveness of the flows, the topography and the availability of sediments from hillslopes. The sediment load was dominated by winter and spring seasons accounting for 89% of the annual load. A high sediment supply in winter might confirm the intense geomorphic action caused by high intensity rainfall, low vegetation cover, and heavy machine activity in the agricultural fields. Following watershed management for local communities may bring multiple benefits. The adoption of suitable measures for soil conservation should reduce soil erosion and improve the livelihoods of the inhabitants. This study can serve as a reference for policymakers and planners.